2009
DOI: 10.1128/jvi.01491-09
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis and Structural Modeling of Human APOBEC3G Reveal the Role of Evolutionarily Conserved Elements in the Inhibition of Human Immunodeficiency Virus Type 1 Infection and Alu Transposition

Abstract: Retroelements are important evolutionary forces but can be deleterious if left uncontrolled. Members of the human APOBEC3 family of cytidine deaminases can inhibit a wide range of endogenous, as well as exogenous, retroelements. These enzymes are structurally organized in one or two domains comprising a zinc-coordinating motif. APOBEC3G contains two such domains, only the C terminal of which is endowed with editing activity, while its N-terminal counterpart binds RNA, promotes homo-oligomerization, and is nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
83
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 67 publications
11
83
1
1
Order By: Relevance
“…Several lines of evidence suggest that encapsidation of hA3G involves binding to packaged RNA (26), and it has also been proposed that hA3G dimerization is important in hA3G packaging (21,27,28). We noted a stretch of aromatic residues in the mA3 C-terminal domain, i.e., Y310-F-H-W313, and, nearby in the model structure, a stretch of nine residues, six of which are arginines (R364-R-T-Q-R-R-L-R-R372).…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence suggest that encapsidation of hA3G involves binding to packaged RNA (26), and it has also been proposed that hA3G dimerization is important in hA3G packaging (21,27,28). We noted a stretch of aromatic residues in the mA3 C-terminal domain, i.e., Y310-F-H-W313, and, nearby in the model structure, a stretch of nine residues, six of which are arginines (R364-R-T-Q-R-R-L-R-R372).…”
Section: Resultsmentioning
confidence: 99%
“…The resistance of human A3G to SIVagm Vif could serve as an effective barrier and may explain why SIVagm has not colonized humans. Several studies have shown that A3G residue 128 directly affects the binding of HIV-1 and SIVagm Vif to their respective A3G proteins, suggesting that this residue is part of the Vif binding site (19,20,22,24,25). However, adjacent amino acids, such as those at positions 129 and 130, appear to also be required for HIV-1 Vif/A3G binding (25)(26)(27), and A3G position 130 is also involved in African green monkey subspecies-specific adaptions to Vif degradation (15).…”
mentioning
confidence: 99%
“…The observation that Bet prevented A3G dimerization allowed us to identify relevant residues in A3G regulating the Bet interaction. Amino acids in the putative A3G dimer interface were recently described (36,46), so we tested the Y124A, Y125A, F126L, and W127A A3G mutants (36) that partake in stabilizing the A3G dimer for interaction with Bet. Of these mutants, the W127A mutant is unable to homodimerize and to inhibit HIV-1 ⌬vif due to a lack of encapsidation (36,46).…”
Section: Resultsmentioning
confidence: 99%
“…Amino acids in the putative A3G dimer interface were recently described (36,46), so we tested the Y124A, Y125A, F126L, and W127A A3G mutants (36) that partake in stabilizing the A3G dimer for interaction with Bet. Of these mutants, the W127A mutant is unable to homodimerize and to inhibit HIV-1 ⌬vif due to a lack of encapsidation (36,46). The Y124A and F126L A3G mutants coimmunoprecipitated with Bet, like wild-type A3G, whereas the F126A and W127A A3G mutants showed partial and complete loss of coimmunoprecipitation, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation